196k views
5 votes
4x – 2 + x = 3x + 8 + 3x​

User Jasmina
by
5.0k points

2 Answers

2 votes

Answer:

-10 = x

Explanation:

1) combine all like terms

bring 4x and "x" to the right side to combine them

if we do this they will become negative

so

-2=3x+8+3x-4x-x

now bring "8" to the left side if we do this 8 will become negative

-8-2=3x+3x-4x-x

now we can combine like terms

-10=6x-5x

-10=x

Hope this helps!

User Aaronc
by
4.7k points
5 votes

4x – 2 + x = 3x + 8 + 3x​

Combine like terms:

4x+x-2=3x+3x+8

5x-2=6x+8

Move 6x to the other side. Sign changes from +6x to -6x.

5x-6x-2=6x-6x+8

5x-6x-2=8

-x-2=8

Move -2 to the other side.

-x-2+2=8+2

-x=10

Multiply both sides by -1.

(-1)(-x)=(10)(-1)

x=-10

Answer: x=-10

User Jotch
by
4.9k points